Legal Force of Power of Attorney Agreement to Sell Joint Property after The Existence of a Marriage Agreement Deed made after The Marriage - Rianzi, Sarifa Dira (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. A Notary is an official who has the authority to make authentic deeds based on the Law on the Position of Notary, the Notary Code of Ethics and other provisions related to the Notary profession. In his authority to make authentic deeds, an example of a deed that can be made by a Notary is a Deed of Power of Attorney for Sale Agreement. In addition to these deeds, a Notary is also blessed to make a Deed of Separation of Property Marriage Agreement which Based on the Decision of the Constitutional Court dated October 27, 2016 Number 69 / PUU-XIII / 2015, a marriage agreement can be made during the marriage and does not harm the interests of the third party involved. And this provision does not apply retroactively, so that assets obtained after marriage and before the separation of property marriage agreement is made remain joint assets. Based on the above, this study aims to determine and analyze the position of marital assets obtained before the deed of separation of assets is made, and to determine and analyze the legal force of the Deed of Power of Attorney to Sell Joint Assets after the making of the Marriage Agreement Deed. The problem is analyzed using the theory of legal certainty. The research approach method used by the author is normative legal research, using qualitative data types and using secondary data sources, which data the author obtained through the data collection process through library research. The data analysis method uses a qualitative analysis method in which the data obtained is arranged systematically and then analyzed qualitatively in order to obtain clarity on the problems to be discussed.Keywords: Authentic Deed; Notary; Power of Approval; Separation of Property Marriage Agreement.